CHARACTERIZATION OF XILANASE ENZYMES OF BACILLUS SUBTILIS AS A BIOBLEACHING AGENT - Devita Sulistiana; Dian Puspita Anggraini; Dwi Kameluh Agustina (JURNAL PENA SAINS, 2021)
Xylanase can be used as an alternative material in the pulp bleaching process to reduce the use of chemicals in the paper industry. Bacillus subtilis is a type of bacteria that can produce xylanase. Xylanase characterization is needed to determine the maximum activity that will be used in the pulp bleaching process. This study aims to determine the xylanase characterization of Bacillus subtilis in terms of optimal pH, optimal temperature, carbon source, and optimal nitrogen source. The research material used was a pure culture of Bacillus subtilis bacteria obtained from the Biochemistry Laboratory of the Department of Chemistry, Faculty of Mathematics and Natural Sciences, Brawijaya University. The characterization of the xylanase enzyme was carried out using the RAL method. The results of characterization of the determination of pH, temperature, carbon source, and nitrogen xylanase source from Bacillus subtilis showed that the optimum conditions for xylanase were at pH 7 with a maximum activity of 5.085 U / mL; the optimum temperature at 40oC with activity 8.017 U/mL; maximum carbon source at a concentration of 15% (b/v) with activity 7.517 U/mL; and the optimum source of nitrogen with a concentration of 0.17% (b/v) with an activity of 4.815 U/mL.